A Revolução das Mochilas no Brasil: viagens e contracultura em tempos ditatoriais - Leon Kaminski (Centre de Recherches sur les Mondes Américains, 2021)
In dictatorial Brazil (1964-1985), marked by repression, travels were incorporated by a part of the youth as a form of resistance to the system and the military regime in the everyday sphere. It aims to demonstrate how the territorial displacement realized by the travelers through the country provided the circulation of the imaginary of the counterculture beyond the capitals and its appropriation by sections of the youth that were not part of major urban centers’ middle class. On one hand, we discuss the repression of the counterculture and travel as a form of resistance to the suffocating daily life of authoritarianism, on the other hand, the ambiguities and contradictions of these practices are demonstrated. To this end, this analysis explores a wide range of sources and investigates travel as a cultural practice, how experience was carried out and lived in that historical, national and international context, as well as its role in the circulation of the imaginary and socio-cultural expressions of the counterculture, revealing its subversive and transformative character, in a liberating perspective.